MENINGKATKAN KETERAMPILAN SOSIAL SISWA KELAS V MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND ROBIN DALAM PEMBELAJARAN IPS - Fajriah, Tsaltsa Nur; Marini, Arita; Sarifah, Iva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students’ social skills in Social Studies learning through the implementation of the Round Robin cooperative learning model. The background of this research is the low level of students’ social skills, such as lack of cooperation, empathy, assertiveness, and self-control during group discussions. This research is a Classroom Action Research (CAR) conducted in two cycles involving fifth-grade students of SDN Kebon Jeruk 04, West Jakarta. Data were collected through observation, questionnaires, field notes, and documentation, and analyzed using both quantitative and qualitative approaches. The results showed that the Round Robin model was effective in improving students’ social skills. The number of students who scored ≥70 increased from 55.56% in Cycle I to 85.19% in Cycle II. Furthermore, students became more active in expressing opinions, cooperating, and demonstrating mutual respect without dominating the discussion. Based on these findings, the Round Robin model is proven to be suitable for use in Social Studies learning as a means of developing elementary school students’ social skills.